If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -7 = a Combine like terms: 20 + -7 = 13 13 = a Solving 13 = a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 13 + -1a = a + -1a Combine like terms: a + -1a = 0 13 + -1a = 0 Add '-13' to each side of the equation. 13 + -13 + -1a = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -1a = 0 + -13 -1a = 0 + -13 Combine like terms: 0 + -13 = -13 -1a = -13 Divide each side by '-1'. a = 13 Simplifying a = 13
| 0.47-1.56=b | | 14xcos(55)= | | 4(2y-4y)+2y=24 | | 23x-5=22x+5 | | 20u-u+2u-18u=18 | | 14-3m=33 | | 62=-8 | | N^3-4N-2N^2+8=XN+2X | | 5x12/10 | | 5x+(x+6)=90 | | (x^5)^13/30 | | (-11m)-(-2m)= | | 7f(x)=6(x)+3 | | -18=-2(4y+1) | | 3.75+3.7=1.7+1.75 | | 4(c+2)+10=2c-6 | | 13n=5 | | (-11m)-2m= | | 27=90+c | | -2x-77=-11x+40 | | 3x=108solver | | 12w-6w-3w=12 | | 10x-73=71 | | 3(v-6)-8=-7(-2v+4)-3v | | 24=96n | | 15x-27=42-8x | | -81=3x | | 2(x-1)+3(2x-1)=7 | | a+(b+12)= | | 12-d=5 | | 2x*x=92 | | 2(21.5-2.5y)+5y=43 |